The influence of the training of coping skills for stress on self-control and intensity of depression among adolescents with suicide risk - Keliat, Budi Anna; Tololiu, Tinneke Aneke; Daulima, Novy Helena Catharina; Erawati, Erna (International Journal of Advanced Nursing Studies, 2015)
Background: Suicide was the second leading cause of death among 15–29 year-olds globally in 2012. While the key elements in developing a national suicide prevention strategy not only the health sector but also education so far the training of coping skills for stress was not being a part of health school program to prevent suicide.Objective: This study conducted to explore the training of coping skills for stress on self-control and intensity of depression among adolescents with suicide risk.Method: This research design using a quasi-experimental pre-posttest with control group. The sample consisted of each 40 adolescents in the intervention group and in the control group.Results: We found that the adolescent’s self-control and the intensity of depression was improved significantly in the intervention group.Conclusion: The training of coping skills for stress appears to be effective in increasing self-control and decreasing intensity of depression. We recommended that the training of coping skills for stress for adolescents should become a health school program in suicide prevention.